Marine algae of the Sulu Sea Islands, Philippines II: annotated list of the brown seaweeds (Phaeophyceae) from the Cuyo Islands - Liao, Lawrence M.; Belleza, Dominic Franco C.; Geraldino, Paul John L. (Phytotaxa, 2013)
The western section of the Philippine archipelago comprising the frontier island of Palawan and numerous islands within the vast Sulu Sea basin is least known in terms of its marine biota. The Smithsonian Institution Philippines Expedition (SIPHILEXP) collected thousands of marine samples to document the rich marine biodiversity there. Collections of marine benthic algae were made from the small islets of the Cuyo Islands located in the northern section of the Sulu Sea. This paper documents 17 species and one form of brown algae (Phaeophyceae) grouped into nine genera and five families. All except three taxa are new records for the locality. The classification and nomenclature of each species follow currently accepted systems. Extensive remarks on the peculiarities of each species are provided. Compared to the marine flora of other regions of the Indo-Pacific, the brown algal flora of the Cuyo Islands is potentially as diverse, but owing to some species that are commonly found elsewhere and were not accounted for in this survey, the rich diversity of the marine flora here cannot be fully appreciated. The available information represents a valuable contribution to the knowledge of marine brown algal diversity in this poorly known region of the Philippines.